Contextual teaching and learning (CTL) as a strategy to improve students mathematical literacy. (July 2020) - Afni, N; Hartono,
Abstract: Mathematical literacy is defined as solving and using mathematics in various problems to solve problems in real life. This problem begins with identification and problem solving. Students will easily understand mathematics by applying their knowledge in various situations or contexts. this ability can be trained through Contextual teaching and Learning (CTL). This approach is one of the strategies that can improve students' mathematical literacy. Because CTL can be used to connect real-world situations with mathematics so students can understand and solve problems. CTL is recommended to make students use mathematical knowledge in understanding, solving problems and communicating. However, not many teachers are aware that increasing students' literacy skills can use CTL. Learning mathematics using this context is a means of increasing students' mathematical knowledge. Students will be helped and feel happy when learning mathematics related to the context that exists in everyday life. Therefore, the use of contextual learning strategies is very important for teachers and students in improving mathematical literacy skills.